Effect of drying and storage on antioxidant activity parameters of celery, parsnip and root parsley chips - V. A. Kharchenko; N. А. Golubkina; A. I. Moldovan; V. I. Tereshonok; V. А. Zayachkovsky; M. S. Antoshkina; V. А. Stepanov; L. V. Pavlov (Овощи России, 2024)
Vegetable chips are extremely popular due to high content of antioxidants, valuable biological activity and long-term storage. During the investigation optimal methods of drying and chips storage from celery (Egor and Dobrynya cvs), parsnip (Krugly, Bely aist and Zhemchug) and parsley (Zolushka cv) roots were developed using the criteria parameters of taste, aroma, color and antioxidant content. The highest organoleptic properties were recorded for celery chips of Dobrynya cv, parsnip chips of Krugly cv and root parsleyThe highest differences in chips organoleptic parameters between convectional and freeze-drying methods reached 1.5 times for parsnip Bely aist cv. while the lowest differences were recorded for root parsley (1.05 times). Decrease in antioxidant activity during freeze-drying was the lowest in root parsley and celery Dobrynya cv. Convectional drying did not affect chips total antioxidant activity and demonstrated the highest preservation effect after 8 months storage. On the contrary, vitamin C losses were the highest during convectional drying though during storage vitamin C content in such chips decreased much less than in freezedried products. Aluminum foil provided 1.2-1.8 times higher content of antioxidants than paper and polyethylene package. Significant inter species and varietal differences in antioxidant stability during various methods of drying and storage were revealed.